Ecological and environmental damage assessment of water resources protection mining in the mining area of Western China. (June 2022) - Huang, Yanli; Wang, Jiaqi; Li, Junmeng; Lu, Mingyin; Guo, Yachao; Wu, Laiwei; Wang, Qingxiong
Highlights: Establish an ecological evaluation index system based on water preserved mining. Use DEMATEL theory to realize the relationship analysis between indicators. Propose the subjective and objective weight method of DEMATEL-entropy method. Cloud model is introduced to construct the eco-environment cloud evaluation model. Verify the rationality of the cloud evaluation model through example. Abstract: The application of water resources protection mining has alleviated greatly the deterioration of ecological environment in the ecologically fragile mining areas of Western China. To quantitatively evaluate the improvement effect of this technology on the ecological environment of the mining area, the evaluation index system of ecological environment in the mining area was proposed based on the water-preserved mining techniques of water resources protection mining. The entropy weight method and the Decision-making Trial and Evaluation Laboratory were selected as the subjective and objective weight method, and the cloud model theory was used as the modeling basis, then a quantitative evaluation model of ecological environment of water-preserved mining was constructed. Besides, the Halagou coal mine in Shendong Group was taken as an example, and the ecological environment of this mining area was quantitatively assessed to verify the rationality of the proposed evaluation model. The results show that the ecological environment level of the Halagou mining area is between Excellent and Good (generally at a good level), which is consistent with the actual ecological environment situation of the Halagou mining area. Thus, the rationality of the proposed evaluation model is verified. Through the evaluation cloud map, the evaluation results are biased towards the evaluation level of Good, indicating that there is still room for improvement in the ecological environment of the Halagou coal mine. Combined with the analysis results, suggestions for the sustainable improvement of the ecological environment of the mining area are given: Halagou coal mine should focus on the restoration of subsidence area and the control of mine water inflow.